The historical Jesus and the search for God - Patterson, Stephen J. (Hervormde teologiese studies, 1998)
Since the advent of the first quest for the historical Jesus in the nine-teenth century, theologians have felt compelled to accept as normative either the Jesus of history (so Liberal Theology) or the Christ of faith (so Liberal Theology). This choice is a false one, for the structure of early Christian faith involves both historical and confessional elements inthe creation of meaningful theological discourse. We can recover the poetics of that discourse if we clearly distinguish between the historical and confessional elements in the gospels, and place them once again in a dialectical relationship. In this way, the quest for the historical Jesus may retain its character as an historical discipline, and yet still prove fruitful for critical theological reflection.